2016
DOI: 10.1186/s40478-016-0363-y
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting rodent models: Octodon degus as Alzheimer’s disease model?

Abstract: Alzheimer’s disease primarily occurs as sporadic disease and is accompanied with vast socio-economic problems. The mandatory basic research relies on robust and reliable disease models to overcome increasing incidence and emerging social challenges. Rodent models are most efficient, versatile, and predominantly used in research. However, only highly artificial and mostly genetically modified models are available. As these ‘engineered’ models reproduce only isolated features, researchers demand more suitable mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 60 publications
(69 reference statements)
5
23
0
Order By: Relevance
“…Altogether these data suggest that no AD-related pathology can be found in aged octodons, in conflict with previous reports567, but in accordance with a more recent contribution8.…”
Section: Resultssupporting
(Expert classified)
See 3 more Smart Citations
“…Altogether these data suggest that no AD-related pathology can be found in aged octodons, in conflict with previous reports567, but in accordance with a more recent contribution8.…”
Section: Resultssupporting
(Expert classified)
“…Overall, our investigation has not unveiled any specific pattern of age-related pathology therefore questioning the relevance of such rodent as a natural model for age-related disorders. Interestingly, a recent study came to the same conclusions with the same groups of age while focusing on AD-related pathology8. Although the common max life expectancy is 3–4 years in the wild, captivity allows prolonged life span up to 5–8 years, thus suggesting that our age-groups are relevant for the study of age-related phenomenons817.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Some studies have found that Octodon degu have intracellular and extracellular accumulation of Aβ, plaques at old ages, intracellular tau accumulation, astrocytosis, synaptic changes and memory impairment that correlates with increased levels of oligomers (reviewed in [16, 131]). However this pathology appears to be inconsistent as other studies do report any AD associated pathology in aged animals [149]. …”
Section: Physiological Modelsmentioning
confidence: 81%